Perancangan Ulang Alat Pengupas Kacang Koro Pedang Rotaris Disc dengan Metode Triz - Wahyu Sri Wulandari; Hadi Santosa; Julius Mulyono (Widya Teknik, 2021)
Sword koro (Canavalia ensiformis) is one of the local beans commonly used by the community as raw material for making tempeh. Sword M. pruriens have the advantage of being easily cultivated because they are acid-resistant and dry-resistant (Gozal, 2015). In its processing, the M. pruriens contain cyanogen glucoside (HCN) so that when consumed directly it will have a negative effect on the body. The content can be removed by heating, soaking and fermenting. Besides the processing of beans, the other most important part is the stripping process. The epidermis of the koro sword is thick enough so that if it is done traditionally it will result in fatigue for workers and requires a long time. In previous studies that have been carried out there are deficiencies in previous tools that need to be repaired, and therefore will be redesigned on these tools. Some of these parts include the dimensions of the tool, stripping space, and the position of the lever that is not right. As the main media for peeling the koro sword. By considering using anthropometric data and the TRIZ method as a medium for designing the koro sword paring tool, a solution has been obtained. The dimensions and position of the parts used are in accordance with the average height of the human body in Indonesia and the stripping space is changed from vertical to horizontal with a rotary disc.